Universal dimensional crossover of domain wall dynamics in ferromagnetic films - Torres, W. Savero (2019)
The magnetic domain wall motion driven by a magnetic field is studied in (Ga,Mn)As and (Ga,Mn)(As,P) films of different thicknesses. In the thermally activated creep regime, a kink in the velocity curves and a jump of the roughness exponent evidence a dimensional crossover in the domain wall dynamics. The measured values of the roughness exponent ζ1d=0.62±0.02 and ζ2d=0.45±0.04 are compatible with theoretical predictions for the motion of elastic line (d=1) and surface (d=2) in two- and three-dimensional media, respectively.